The Use of AEGISUB to Improve EFL Listening Comprehension - Nendriliana Dyah Puspitorini (Manajemen Pendidikan, 2020)
Listening is the skill to understand and identify what the speaker says. In listening, students should sensibly in hearing the information. This paper aims to describe the difficulties in listening in creating subtitling and problems faced in creating subtitle use Aegisub. The population of this research was twenty Indonesian EFL learners studying at an Islamic university in Central Java, Indonesia. The type in this paper was used a qualitative method. In addition, the research data were collected by observation, interview and document analysis. This research found three problems in listening. In listening there are speed rate, pronunciation and too noisy) and three problems in using Aegisub, there are synchrony time, application problem and The result shows the difficulties in listening when creating subtitle and problems in using Aegisub as they applied Aegisub.